The Pressure Is On – Epiphyte Water-Relations Altered Under Elevated CO2 - Batke, Sven; Holohan, Aidan; Hayden, Roisin; Fricke, Wieland; Porter, Amanda Sara; Evans-Fitz.Gerald, Christiana Marie (Frontiers in Plant Science, 2018)
Vascular epiphytes are a major biomass component of forests across the globe and they contribute to 9% of global vascular plant diversity. To improve our understanding of the whole-plant response of epiphytes to future climate change, we investigated for the first time both individual and combined effects of elevated CO2 (560 ppm) and light on the physiology and growth of two epiphyte species [Tillandsia brachycaulos (CAM) and Phlebodium aureum (C3)] grown for 272 days under controlled conditions. We found that under elevated CO2 the difference in water loss between the light (650 µmol m-2s-1) and shade (130 µmol m-2s-1) treatment was strongly reduced. Stomatal conductance (gs) decreased under elevated CO2, resulting in an approximate 40-45% reduction in water loss over a 24h day/night period under high light and high CO2 conditions. Under lower light conditions water loss was reduced by approximately 20% for the CAM bromeliad under elevated CO2 and increased by approximately 126% for the C3 fern. Diurnal changes in leaf turgor and water loss rates correlated strong positively under ambient CO2 (400 ppm) and high light conditions. Future predicted increases in atmospheric CO2 are likely to alter plant water-relations in epiphytes, thus reducing the canopy cooling potential of epiphytes to future increases in temperature.